2018
DOI: 10.24198/jkp.v6i1.390
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sundanese Kacapi Suling “Ayun Ambing” Music Therapy to The Level of Anxiety on Chronic Renal Failure Patient Undergoing Hemodialysis

Abstract: One of the most common psychological problems found in patients with chronic renal failure (ESRD) undergoing hemodialysis is anxiety. Unresolved anxiety can have a negative impact on physiological and psychological conditions that can aggravate the condition of the disease. Traditional Sundanese music therapy Kacapi Suling "Ayun Ambing" has a slow tempo and soft so that it can be used as a therapy. The design used was a Quasy Experimental, with a pretest-posttest control group design approach, involved 46 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In Indonesia, a research using traditional music was shown on Alamsah et al (2018) study. They used music from Kacapi Suling "Ayun Ambing" that gave influence to anxiety on patients who were doing hemodyalisis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Indonesia, a research using traditional music was shown on Alamsah et al (2018) study. They used music from Kacapi Suling "Ayun Ambing" that gave influence to anxiety on patients who were doing hemodyalisis.…”
Section: Discussionmentioning
confidence: 99%
“…Hillers Maumere. Based on the research of Alamsah et al (2018), the standard deviation was obtained (5.29) and the minimum difference (4.51). Then the sample size needed in this study: n1=n2= 14.44.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on instrumental Sundanese music, especially the flute lute, can relieve post-cesarean surgery wound pain, relieve acute pain in the elderly, and reduce anxiety levels in hemodialysis patients. (Alamsah et al, 2018),(Marsyia & Widyatuti, 2020)(Sepriliani et al, 2018)…”
Section: Discussionmentioning
confidence: 99%
“…(Wasta & Sholihat, 2020). Several studies on the harp flute as music therapy include the study ofSepriliani, Mulyani, & Diana (2018), this has been proven to relieve pain in post partum wounds, relieve acute pain in the elderly, especially by looking at a decrease in blood pressure and pulse (Marsyia & Widyatuti, 2020), reducing anxiety levels in hemodialysis patients (Alamsah, Rahayuwati, & Purba, 2018). Various articles about herbal drinks that can reduce pain have also been started, one of which is a drink from ginger, cinnamon, and honey.…”
Section: Introductionmentioning
confidence: 99%